Perilaku Beragama dalam Memaknai Ritual Budaya (Analisis Perlaku Sosial dalam Ritual Keagamaan di Masyarakat) - Aziz Muslimin (Universitas Muhammadiyah Makassar, 2017)
Abstract. Religion is not only something that is doctrinal-ideological and abstract acutely, but it is formed in the form of matter, that is in everyday life. Religion which is the source of motivation of individual action in social relations. Muslims in this country will be more receptive, and make the difference as a blessing not anathema. That is the moderate substance that promotes mutual respect for diversity within a person can be muffled with the understanding of others / differences.Keywords: Social Behavior, Ritual, Religious.